Use the product rule to differentiate the given function with respect to x: x^2(x+3)^4 u=x^2 v=(x+3)^4 du/dx=2x dv/dx=4 y=4x^2+2x(x+3)^4 I do not know how to get to the answer from here but the answer is 6x(x+1)(x+3)^3
Follow Math Help Forum on Facebook and Google+
Originally Posted by juliak Use the product rule to differentiate the given function with respect to x: x^2(x+3)^4 u=x^2 v=(x+3)^4 du/dx=2x dv/dx=4 y=4x^2+2x(x+3)^4 I do not know how to get to the answer from here but the answer is 6x(x+1)(x+3)^3 Your dv/dx is incorrect
Your dv/dx should read
View Tag Cloud